The idea of economic development: Views from Africa - Hippolyte Fofack (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Although development generally refers to a broad concept, the quest for development in Sub-Saharan Africa has been biased by ideological considerations which made abstraction of local conditions and people's aspirations. The prevalent development models have used increased national income as a sufficient statistics for broad-based development. This paper argues for an alternative and a more comprehensive and reflexive development framework that harnesses local and global knowledge and advocates generalized balanced growth and structural transformation to move Sub-Saharan African countries towards self-reliance - their collectively defined aspirational goal. Analytically, it shows that the potential development outcomes of the region under such an endogenous framework would be superior to the results achieved under the prevailing development models.
Keywords: B10; N17; O11; O41; 330; regional integration; regulatory reform; competitiveness; Africa